The perception of risk in contracting and spreading COVID-19 amongst individuals, households and vulnerable groups in England: a longitudinal qualitative study - Kerry Hanna; Pam Clarke; Kerry Woolfall; Shaima Hassan; Katharine Abba; Taghreed El Hajj; Elizabeth Deja; Saiqa Ahmed; Neil Joseph; Adele Ring; Gerry Allen; Paula Byrne; et al. (BMC, 2023)
Abstract Background Social distancing restrictions to manage the COVID-19 pandemic were put in place from March 2020 in the United Kingdom (UK), with those classed as "highly clinically vulnerable" advised to shield entirely and remain at home. However, personal risk perception has been shown to comprise of various elements beyond those outlined in the national pandemic guidance. It is unclear whether those deemed COVID-19 vulnerable identified as high-risk to COVID-19 and thus complied with the relevant advice. The aim of this research is to explore the perception of risk in catching and spreading COVID-19, amongst individuals from individual households, and vulnerable groups in a region of the UK. Methods Two individual, semi-structured interviews were conducted, four-weeks apart, with adults living in households in the Liverpool City Region. At the follow-up interview, participants were given the option of using photo-elicitation to guide the discussion. Reflexive thematic analysis was employed to conceptualise themes. The qualitative analysis was underpinned with symbolic interactionism. Results Twenty-seven participants (13:14 males:females, and 20 with a vulnerable risk factor to COVID-19) completed a baseline interview, and 15 of these completed a follow-up interview four-weeks later. Following thematic analysis, two overarching themes were conceptualised, with subthemes discussed: theme 1) Confusion and trust in the risk prevention guidance; and theme 2) Navigating risk: compliance and non-compliance with public health guidance. Conclusion Participants developed their own understanding of COVID-19 risk perception through personal experience and comparison with others around them, irrespective of vulnerability status. COVID-19 guidance was not complied with as intended by the government, and at times even rejected due to lack of trust. The format in which future pandemic guidance is conveyed must be carefully considered, and take into account individuals' experiences that may lead to non-compliance. The findings from our study can inform future public health policy and interventions for COVID-19 and future pandemics.